Screening of depression with an assessment of the socioeconomic status of patients in the primary care network in the large industrial city of Eastern Siberia - R. D. Peskovets; S. Yu. Shtarik; A. A. Evsyukov (Бюллетень сибирской медицины, 2020)
The aim was to compare the relationship between the severity of depression symptoms among the unorganized population of Krasnoyarsk in 2006 and 2012 with respect to socioeconomic and demographic factors; and to compare their prevalence for the analyzed period.Materials and methods. Two sample groups were selected from the unorganized population that resided permanently in the territory of Krasnoyarsk in 2006 and 2012. Evaluation of the severity of depression in both cases was carried out according to the Hospital Anxiety and Depression Scale, Depression subscale (HADS-D). Results. In both sample groups, the frequency of depression was associated with age. In 2012, social and economic factors of depression were revealed: lack of higher education, widowhood, unemployment and family poverty. A significant decrease in the frequency of increased (39.1% vs 16.4%) and clinical depression (14.6% vs 4.5%) was found for the period from 2006 to 2012. Conclusions. In 2012, the frequency of the above-normal depression level according to HADS-D in working age population was largely determined by the influence of socioeconomic factors. A decrease in the frequency of increased and clinical levels of depression among the adult population of Krasnoyarsk over the period from 2006 to 2012 was established.